Critical Success Factors Of Customer Relationship Management At Private Hospitals In Malaysia - Abdullah, Kamarul Zaman (2005)
The purpose of this study is to explore the critical success factors of Customer Relationship Management (CRM) in Malaysian private hospitals. After reviewing the related literatures about CRM success factors, it was found out that the among critical success factors are the top management support, technological readiness, and knowledge management capability are the independent variables that the researcher is interested to study. These are main factors that were defined by Croteau and Li (2003).